2016
DOI: 10.1016/j.ultrasmedbio.2015.11.027
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Droplet Composition on Nanodroplet-Mediated Histotripsy

Abstract: Nanodroplet-mediated histotripsy (NMH) is a targeted ablation technique combining histotripsy with nanodroplets that can be selectively delivered to tumor cells. In two previous studies, polymer-encapsulated perfluoropentane nanodroplets were used to generate well-defined ablation similar to that obtained with histotripsy, but at significantly lower pressure, when NMH therapy was applied at a pulse repetition frequency (PRF) of 10 Hz. However, cavitation was not maintained over multiple pulses when ultrasound … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
52
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 24 publications
(60 citation statements)
references
References 32 publications
(56 reference statements)
6
52
0
Order By: Relevance
“…Fractionation of the RBCs turns the color of the embedded cell layer from opaque red to translucent as the RBCs are lysed, which allows direct visualization of the histotripsy-induced fractionation process (Maxwell et al , 2010b; Lin et al , 2014; Vlaisavljevich et al , 2016a; Vlaisavljevich et al , 2013a; Wang et al , 2012). Previous studies have also shown that the lesion visualized in RBC phantoms is similar to the lesion generated in tissue identified by histology (Maxwell et al , 2010b; Lin et al , 2014; Wang et al , 2012).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fractionation of the RBCs turns the color of the embedded cell layer from opaque red to translucent as the RBCs are lysed, which allows direct visualization of the histotripsy-induced fractionation process (Maxwell et al , 2010b; Lin et al , 2014; Vlaisavljevich et al , 2016a; Vlaisavljevich et al , 2013a; Wang et al , 2012). Previous studies have also shown that the lesion visualized in RBC phantoms is similar to the lesion generated in tissue identified by histology (Maxwell et al , 2010b; Lin et al , 2014; Wang et al , 2012).…”
Section: Methodsmentioning
confidence: 99%
“…In intrinsic threshold histotripsy, a single pulse (≤2 cycles) with a single dominant negative pressure phase at very high pressure is used to form a bubble cloud directly from the negative pressure of the incident wave (Lin et al , 2014; Maxwell et al , 2013; Vlaisavljevich et al , 2015b). Using the short pulses for intrinsic threshold histotripsy, cavitation initiation depends on the amplitude and duration of the applied negative pressure as well as the properties of the media (Vlaisavljevich et al , 2015a; Vlaisavljevich et al , 2016a; Vlaisavljevich et al , 2016b; Vlaisavljevich et al , 2015b; Maxwell et al , 2013; Vlaisavljevich et al , 2013a). Previous work has measured the intrinsic threshold of water-based soft tissues and tissue phantoms to be ~25–30 MPa at ultrasound frequencies ranging from 345 kHz to 3 MHz (Maxwell et al , 2013; Vlaisavljevich et al , 2015b).…”
Section: Introductionmentioning
confidence: 99%
“…Exogenous nuclei reduce the threshold for histotripsy-induced bubble nucleation (Vlaisavljevich et al 2013a), thereby reducing the overall bubble size (Bader 2018). The change in bubble dynamics with exogenous nuclei consequently reduces the efficacy of tissue ablation (Vlaisavljevich et al 2016a).…”
Section: Change Thy Liquidmentioning
confidence: 99%
“…A larger number of pulses are required for complete liquefaction of the focal zone for NMH than for insonation without droplets, indicating the smaller size of bubbles nucleated from droplets compared with intrinsic nuclei. Sustainable droplet nucleation is dependent on the boiling temperature of the perfluorocarbon (Vlaisavljevich et al 2016a). At peak negative pressures above the threshold for bubble cloud formation, cavitation is sustained for only 10 pulses for droplets formed with perfluoropentane (boiling point of 29˚C).…”
Section: Change Thy Liquidmentioning
confidence: 99%
“…Moreover, we aimed to develop a new system for cancer treatment, using direct low-dose antitumor agent administration (Ashida et al 2015;Kawabata et al 2013Kawabata et al , 2014. No other studies on cancer treatments, using tissue fractionation at such a low intensity with the aid of PCNDs seem to have succeeded, although the effects of nanodroplets on histotripsy have been investigated with tissue-mimicking phantoms for drug delivery purposes (Vlaisavljevich et al 2015(Vlaisavljevich et al , 2016.…”
Section: Introductionmentioning
confidence: 99%